2015
DOI: 10.2967/jnumed.115.156794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-Labeled Fluoroalkylphosphonium Cations with 13N-NH3 for PET Myocardial Perfusion Imaging

Abstract: Despite substantial advances in the diagnosis of cardiovascular disease, there is a need for 18 F-labeled myocardial perfusion agents for the diagnosis of ischemic heart disease because current PET tracers for myocardial perfusion imaging have a short half-life that limits their widespread clinical use in PET. Thus, 18 F-labeled fluoroalkylphosphonium derivatives ( 18 F-FATPs), including (5-18 F-fluoropentyl)triphenylphosphonium cation ( 18 F-FPTP), (6-18 F-fluorohexyl)triphenylphosphonium cation ( 18 F-FHTP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In a preclinical study appearing in this issue of The Journal of Nuclear Medicine, Kim and colleagues assess the suitability of 3 18 F-labeled fluoroalkylphosphonium salts for PET myocardial perfusion imaging (11). Similar to 99m Tc-sestamibi and 99m Tc-tetrofosmin, these moieties depend on high mitochondrial membrane potentials for retention in cardiac myocytes.…”
Section: F-labeled Fluoroalkylphosphonium Salts For Perfusion Imagingmentioning
confidence: 99%
“…In a preclinical study appearing in this issue of The Journal of Nuclear Medicine, Kim and colleagues assess the suitability of 3 18 F-labeled fluoroalkylphosphonium salts for PET myocardial perfusion imaging (11). Similar to 99m Tc-sestamibi and 99m Tc-tetrofosmin, these moieties depend on high mitochondrial membrane potentials for retention in cardiac myocytes.…”
Section: F-labeled Fluoroalkylphosphonium Salts For Perfusion Imagingmentioning
confidence: 99%
“…Figure 1) [1315]. It was also shown that 18 F-FPTP has greater first-pass myocardial extraction than 13 N-ammonia in isolated perfused rat heart, indicating the suitability of 18 F-FPTP as a quantitative myocardial PET imaging agent [14, 15]. In addition, no metabolite was detected in the serum of mice 30 min after intravenous injection of 18 F-FPTP, implying that the metabolite correction would not be necessary in the kinetic analysis of 18 F-FPTP myocardial PET data [13].…”
Section: Introductionmentioning
confidence: 99%
“…PET-measured MBF has shown excellent agreement with that measured by microsphere injection and invasive activity measurement (18)(19)(20)(21)(22). MBF can be measured by compartment modeling and estimation of rate constant values among tissue compartments ( Fig.…”
Section: Ffr Vs Mbfmentioning
confidence: 83%